2008
DOI: 10.1099/mic.0.2007/011445-0
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol tolerance of sugar transport, and the rectification of stuck wine fermentations

Abstract: The incomplete consumption of sugar resulting from stuck wine fermentation is associated with important economic losses. One of the solutions to this serious problem consists of reinoculating the brew with a yeast starter culture that is both alcohol tolerant and a vigorous fructose fermenter. The present work aimed to select yeast strains capable of restarting stuck wine fermentations, and identify key parameters that contribute to the efficiency of the strains. Commercial and non-commercial Saccharomyces win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 41 publications
7
49
1
3
Order By: Relevance
“…2c, d). Arrizon et al (2006) and Berthels et al (2004) also observed that the performance of S. cerevisiae strains largely depends on the fermentation substrate (agave or grape musts), the location where they were isolated, the temperature (Tronchoni et al 2009), which was rather high in our case, the physiological state (exponential or stationary) of the inocula (Santos et al 2008) and also on the kinetic properties of the in vivo fructose phosphorylation once it has been taken up by the yeast (Berthels et al 2008). However, it was intriguing that the Fermichamp strain was unable to consume all of the glucose in the M3 medium, contrary to the results reported by Guillaume et al (2007) in a synthetic must medium (MS300) with the same G/F initial ratio and concentration and a similar temperature (28°C).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…2c, d). Arrizon et al (2006) and Berthels et al (2004) also observed that the performance of S. cerevisiae strains largely depends on the fermentation substrate (agave or grape musts), the location where they were isolated, the temperature (Tronchoni et al 2009), which was rather high in our case, the physiological state (exponential or stationary) of the inocula (Santos et al 2008) and also on the kinetic properties of the in vivo fructose phosphorylation once it has been taken up by the yeast (Berthels et al 2008). However, it was intriguing that the Fermichamp strain was unable to consume all of the glucose in the M3 medium, contrary to the results reported by Guillaume et al (2007) in a synthetic must medium (MS300) with the same G/F initial ratio and concentration and a similar temperature (28°C).…”
Section: Discussionmentioning
confidence: 97%
“…These findings are most likely because these strains have been previously selected based on high fermentation performance and the ability to produce more than 20 mg of ethyl acetate per litre. The fact that mezcal S. cerevisiae strains behaved differently in terms of hexose consumption in medium M3 (G/F = 1:1), compared with the control strain Fermichamp, could be because the latter was isolated from a grape must fermentation and is commercially used to reactivate stuck fermentations, where the glucose concentration is typically minimal or zero and there is a high concentration of both fructose and ethanol, factors that greatly influence the fermentative capabilities of yeast (Santos et al 2008;Arroyo-López et al 2009). The fitted linear (fructose) and logarithmic (glucose) profiles have also been observed by Tronchoni et al (2009), who evaluated the percentage of sugar still remaining in a Tempranillo must fermented by strain S. cerevisiae T73 rather than hexose consumption.…”
Section: Discussionmentioning
confidence: 99%
“…A not uncommon experience for winemakers is a slow and/or incomplete consumption of sugars by yeast during alcoholic fermentation. A stuck fermentation can be caused by various factors, including nutrient limitation, temperature, pH variation, lack of oxygen, presence of toxic compounds and poor ethanol tolerance of the yeast strain (Bisson, 1999;Santos et al, 2008). It is known that the kinetics of sugar consumption by yeast are strongly influenced by transport rate within the cell: hexose transporters, for example, possess greater affinity for glucose than fructose, which explains why, in a stuck fermentation, the residue sugar is mainly fructose (Berthels et al, 2004(Berthels et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Above certain concentrations accepted as normal (0.2 to 0.6 g/l), acetic acid has a negative impact on the organoleptic qualities of wine and may affect the course of fermentation, leading to sluggish or arrested fermentations (Alexandre & Charpentier, 1998;Bely et al, 2003;Santos et al, 2008). In bioethanol production from lignocellulosic acid hydrolysates, acetic acid may also be associated with the inhibition of alcoholic fermentation, limiting the productivity of the process (Lee et al, 1999;Maiorella et al, 1983;Palmqvist & Hahn-Hägerdal, 2000).…”
Section: Introductionmentioning
confidence: 99%